Thresholds for Spinal Anaesthesia-induced Hypotension During Caesarean Section - Gautam, B.; Bhattarai, A. (Kathmandu University Medical Journal, 2021)
Background Spinal anaesthesia is the current standard for caesarean section. Hypotension, a common complication, potentially results in adverse foetal and maternal outcomes. However, hypotension-defining criteria are varied. Objective To identify the blood pressure thresholds for spinal anaesthesia-induced hypotension during caesarean section. Method This is a retrospective cohort study of spinal anaesthesia-induced hypotension that occurred till baby-delivery during caesarean section. Reports on intraoperative hypotension, collected previously from January to December 2019, were reviewed to identify the hypotension-defining thresholds. The thresholds were categorized into systolic blood pressure (SBP) of 80, 90 or 100 mmHg, mean arterial pressure (MAP) of 60, 65 or 70 mmHg, combinations, and others. Parturient and anaesthesia characteristics, and associated hypotensive symptoms were also recorded for descriptive analysis. Result Spinal anaesthesia-induced hypotension was identified in 129 (11.5%) cases among 1116 caesarean sections. Altogether, 12 hypotension-defining thresholds were employed. Thresholds of SBP 90, MAP 60, and SBP 80 mmHg were used in 53 (41%), 28 (21.7%), and 21 (16.2%) cases respectively. Mean maternal age was 28 (±4.22) years and 87 (67.4%) cases underwent emergency surgery. Median sensory blockade level was T4. Nausea-vomiting, bradycardia, and tachycardia were associated during five (3.8%), six (4.6%), and 15 (11.6%) hypotensive incidents respectively. Two cases had unrecordable blood pressure but there was no maternal mortality. Conclusion Systolic blood pressure of 90 mmHg and mean arterial pressure of 60 mmHg included the most common thresholds for spinal anaesthesia-induced hypotension during caesarean section. Identifying the safe and clinically relevant hypotension-defining criteria needs further investigation.